Study of Groundwater Vulnerability to Pollution in the Tambakbayan Watershed in 2006 And 2017 - Widyastuti, Margaretha; Suprayogi, Slamet; Hadi, M Pramono; Christanto, Nugroho; Tivianton, Tommy Andryan; Fadilah, Gita Oktaviani; Rahmawati, Laelina (Jurnal Pendidikan Geografi Gea, 2021)
Tambakbayan is one of the watersheds in Yogyakarta, Indonesia that is experiencing changes in land use. The research aims to analyze the distribution of intrinsic and specific groundwater vulnerability in the watershed that was influenced by land-use changes from 2006 to 2017. The data used are the RBI maps (containinh topographic and land-use information, 2006 and 2017), SRTM imagery, rainfall recorded at the Kambil, Prumpung, Bronggang, Santan, Gemawang, and Karang Ploso stations (2006-2017), soil map, and aquifer map. Land-use change was analyzed by comparing the RBI maps of 2006 and 2017; while the groundwater vulnerability was assessed with the Susceptibility Index a development of the DRASTIC method. The intrinsic groundwater vulnerability was generated based on physical conditions, including depth to the water table, aquifer media, groundwater recharge, and topography, while the specific groundwater vulnerability was a function of these attributes added with one anthropogenic parameter : land-use. Then, all of these parameters were analyzed with map ovelay. The results showed two levels of intrinsic vulnerability : low (2.18% of the watershed area) and medium (97.8%); and three classes of specific vulnerability : low (0.02%), medium (5.06%), and high (94.92%)in 2006. From 2006 through 2017, the areal percentage of the medium vulnerability Â increased, while that of the high vulnerability decreased due to the conversion of agricultural land to a reservoir in 2009.Â